Language change and nineteenth-century science - Watts, Catherine, author.
1 online resource.
Keywords: "Have you ever looked at a word and thought: 'I wonder where that came from'? You might well find the answer in this book which considers the origin and formation of some of the many thousands of new words that were coined in English during the nineteenth century in the broad field of 'science'. Changes in society are often accompanied by the need to find names for such changes which, in turn, have an impact on how the language develops as a result. The British Industrial Revolution ushered in a new era of language change, which led to many new coinages in the English language reflecting scientific knowledge as it developed. Many of these neologisms belong to specialist vocabulary, but others do not and it is these lay coinages which form the focus of this book and are located within their social, cultural and historical backgrounds. Aimed at postgraduate students of the English language and all those interested in the history of the English language, this work explores new worlds and offers an original and fascinating etymological journey through nineteenth-century science in its broadest sense"--